2011
DOI: 10.1128/jcm.05645-11
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus hyicus Bacteremia in a Farmer

Abstract: Bacteria known in animal infectious diseases can cause challenges in human diagnostic laboratories. We present pitfalls in the identification and susceptibility testing of Staphylococcus hyicus , a pathogen that typically causes exudative epidermitis in pigs. In this case, the coagulase-positive staphylococcus isolated from a septic patient was misidentified as Staphylococcus aureus .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
(11 reference statements)
0
19
0
6
Order By: Relevance
“…Coagulase-positive staphylococci other than S. aureus, such as Staphylococcus intermedius and Staphylococcus hyicus have been isolated from the commensal flora of skin and nasopharynx, as well as from infection sites of animals (Quinn et al, 2011) and can be responsible for sepsis (Casanova et al, 2011), nail bed infection (Pottumarthy et al, 2004), and wound infection (Osterlund et al, 1997;Kelesidis and Tsiodras, 2010) in humans following exposure to animals or the pathogens. More importantly, it was observed that coagulase positive Staphylococcus are found in larger proportion (58.1%) of sampled sources, particularly in 61.4% of samples from abattoir environment and 57.5% carcass.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulase-positive staphylococci other than S. aureus, such as Staphylococcus intermedius and Staphylococcus hyicus have been isolated from the commensal flora of skin and nasopharynx, as well as from infection sites of animals (Quinn et al, 2011) and can be responsible for sepsis (Casanova et al, 2011), nail bed infection (Pottumarthy et al, 2004), and wound infection (Osterlund et al, 1997;Kelesidis and Tsiodras, 2010) in humans following exposure to animals or the pathogens. More importantly, it was observed that coagulase positive Staphylococcus are found in larger proportion (58.1%) of sampled sources, particularly in 61.4% of samples from abattoir environment and 57.5% carcass.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the prevalence percentages can also be attributed to the fact that the prevalence of S. saprophyticus changes seasonally and increases significantly at the end of summer [53]. We isolated three coagulase positive Staphylococci, S.aureus, S. intermedius, and S. hyicus (which was found to be MDR), but it is surprising that the second and third are related to dogs and pigs respectively [54,55], and there is no evidence, to the best of our knowledge, that it is part of the natural components of the human's urinary system. S. aureus exhibited significantly lower susceptibility (P≤0.05) to tetracycline, erythromycin, azithromycin, clindamycin, mupirocin, and fusidic acid than CONS.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 It has also been isolated from animals with septic polyarthritis and from bovine mastitis. 29,30 Two cases of human infection, including a donkey biteinduced wound infection 31 and a bacteremia in a farmer, 32 have been reported. To our knowledge, this is the¯rst case of S. hyicus-associated pneumonia.…”
Section: Discussionmentioning
confidence: 99%